Behavioural plasticity and trophic niche shift: How wintering geese respond to habitat alteration. (22nd March 2019) - Lei, Jialin; Jia, Yifei; Wang, Yuyu; Lei, Guangchun; Lu, Cai; Saintilan, Neil; Wen, Li
Abstract: The accelerated rate of human‐induced environmental change poses a significant challenge for wildlife. The ability of wild animals to adapt to environmental changes has important consequences for their fitness, survival, and reproduction. Behavioural flexibility, an immediate adjustment of behaviour in response to environmental variability, may be particularly important for coping with anthropogenic change. The main aim of this study was to quantify the response of two wintering goose species (bean goose Anser fabalis and lesser white‐fronted goose Anser erythropus ) to poor habitat condition at population level by studying foraging behaviour. In addition, we tested whether behavioural plasticity could alter trophic niche. We characterised foraging behaviours and calculated daily home range (HR) of the geese using global positioning system tracking data. We calculated standard ellipse areas to quantify niche width using the δ 13 C and δ 15 N values of individual geese. We linked behavioural plasticity with habitat quality using ANCOVA (analysis of covariance) models. We also tested the correlation between standard ellipse areas and HR using ANCOVA model. We found significant differences in geese foraging behaviours between years in their daily foraging area, travel distance and speed, and turning angle. Specifically, the birds increased their foraging area to satisfy their daily energy intake requirement in response to poor habitat conditions. They flew more sinuously and travelled faster and longer distances on a daily basis. For the endangered lesser white‐fronted goose, all behaviour variables were associated with habitat quality. For bean goose, only HR and turning angle were correlated with habitat quality. The birds, especially the lesser white‐fronted goose, may have had a higher trophic position under poor conditions. Our findings indicate that wintering geese showed a high degree of behavioural plasticity. However, more active foraging behaviours under poor habitat condition did not lead to a broader trophic niche. Habitat availability could be responsible to the divergent responses of foraging HR and isotopic niche to human‐induced environmental change. Therefore, maintaining natural hydrological regimes during the critical period (i.e. September–November) to ensure that quality food resources are available is central to the future of populations of geese within the East Asian–Australasian Flyway.